Creating hierarchical porosity hydroxyapatite scaffolds with osteoinduction by three-dimensional printing and microwave sintering. (14th November 2017) - Pei, Xuan; Ma, Liang; Zhang, Boqing; Sun, Jianxun; Sun, Yong; Fan, Yujiang; Gou, Zhongru; Zhou, Changchun; Zhang, Xingdong
Abstract: Hierarchical porosity, which includes micropores and macropores in scaffolds, contributes to important multiple biological functions for tissue regeneration. This paper introduces a two-step method of combining three-dimensional printing (3DP) and microwave sintering to fabricate two-level hierarchical porous scaffolds. The results showed that 3D printing made the macroporous structure well-controlled and microwave sintering generated micropores on the macropore surface. The resulting hierarchical macro/microporous hydroxyapatite scaffold induced bone formation following intramuscular implantation. Moreover, when comparing the hierarchical macro/microporous hydroxyapatite scaffold to the non-osteoinductive hydroxyapatite scaffolds (either 3D printed or H2 O2 foamed) subjected to muffle sintering which do not have micropores, the critical role of micropores in material-driven bone formation was shown. The findings presented herein could be useful for the further optimization of bone grafting materials for bone regeneration.